A numerical study for effectiveness of a wake equalizing duct - Celik, Fahri (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
A numerical study is carried out for calculating effect of the wake equalizing duct (WED) on the propulsion performance of a chemical tanker. Analysis is performed using a CFD tool based on the solution of Reynolds averaged Navier-Stokes (RANS) equation. Computations are carried out for several arrangements of WED for a number of ship speeds. Total 56 runs are achieved, and the results are compared with each other. It can be concluded from this study that propeller characteristics and resistance of the ship are slightly affected by the presence of the WED, but an additional thrust is produced by the WED. It is also found that the maximum gain obtained by using an appropriate WED design is about 10%. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: wake equalizing duct; energy saving; propeller; propulsion; Engineering; Oceanography